Contact temperatures and their influence on wear during pin-on-disk tribotesting. (February 2015) - Kennedy, Francis E.; Lu, Yuan; Baker, Ian
Abstract: It is important to take contact temperatures into account when developing friction and wear tests for potential tribomaterials and when analyzing the results of those tests. This paper presents some of the most useful analytical and numerical methods that can be used to predict surface temperature rises in dry or boundary lubricated pin-on-disk tribotests. The objective is the development of relatively simple, accurate, and easy-to-use expressions that can be used to predict contact temperatures in pin-on-disk sliding contacts. Results of the methods are compared for several different cases, and experimental verification of the predictions are also presented. The resulting expressions are applied to investigate wear of a ceramic (zirconia), metal (stainless steel) and polymer (polyethylene) in pin-on-disk tests. Highlights: Simplified equations are developed for contact temperature estimation in pin-on-disk testers. Results compare well with contact temperatures determined by finite element analysis. Results clarify wear transitions for intermetallic pins against metallic and ceramic disks. Contact temperatures are used in planning accelerated pin-on-disk tests of polymer pins.